Angiopoietin-Like 4 Mediates PPAR Delta Effect on Lipoprotein Lipase-Dependent Fatty Acid Uptake but Not on Beta-Oxidation in Myotubes - Robciuc, Marius R. (Public Library of Science, 2012)
Peroxisome proliferator-activated receptor (PPAR) delta is an important regulator of fatty acid (FA) metabolism. Angiopoietin-like 4 (Angptl4), a multifunctional protein, is one of the major targets of PPAR delta in skeletal muscle cells. Here we investigated the regulation of Angptl4 and its role in mediating PPAR delta functions using human, rat and mouse myotubes. Expression of Angptl4 was upregulated during myotubes differentiation and by oleic acid, insulin and PPAR delta agonist GW501516. Treatment with GW501516 or Angptl4 overexpression inhibited both lipoprotein lipase (LPL) activity and LPL-dependent uptake of FAs whereas uptake of BSA-bound FAs was not affected by either treatment. Activation of retinoic X receptor (RXR), PPAR delta functional partner, using bexarotene upregulated Angptl4 expression and inhibited LPL activity in a PPAR delta dependent fashion. Silencing of Angptl4 blocked the effect of GW501516 and bexarotene on LPL activity. Treatment with GW501516 but not Angptl4 overexpression significantly increased palmitate oxidation. Furthermore, Angptl4 overexpression did not affect the capacity of GW501516 to increase palmitate oxidation. Basal and insulin stimulated glucose uptake, glycogen synthesis and glucose oxidation were not significantly modulated by Angptl4 overexpression. Our findings suggest that FAs-PPARdelta/RXR-Angptl4 axis controls the LPL-dependent uptake of FAs in myotubes, whereas the effect of PPAR delta activation on beta-oxidation is independent of Angptl4.